Better safe than sorry? Police officers’ identification of and responses to vulnerable crime victims - Raaijmakers, Niels (Policing and society, 2024)
This study addresses police officers’ identification of vulnerable victims and responses to these victims. Using an Articulated Thoughts in Simulated Situations (ATSS) approach, police officers (n = 51) responded to two scenarios regarding a victim who reported either a property crime or a stalking incident. After hearing each scenario, participants judged whether the victim was vulnerable or not and discussed which they would propose any protection measures. Findings showed that a majority of the participants identified the victim as vulnerable. Participants mainly based their judgements on indicators related to the incident or its consequences. Regardless of their judgement, participants proposed a variety of protection measures. Both this finding and the majority of vulnerability judgements suggest that police officers may act out of the principle of ‘better safe than sorry’.